All’s well that ends well - Shakespeare, William (Cambridge University Press, 2003)
This dark comedy, written in the very early 1600s, is the latest title in the revamped "Pelican Shakespeare" series, which offers definitive texts of the plays with scholarly introductions, essays, and notes. You can't go wrong with this wonderful series